Logic Modeling Methods in Program Evaluation - Daniela C. Schröter; Jessica L. Urschel (The Evaluation Center at Western Michigan University, 2008)
A review of the book Logic Modeling Methods in Program Evaluation by Joy A. Frechtling published in 2007 by Jossey-Bass.